Strengthening Legal Awareness in Mitigation: Education and Community Empowerment Study Based on Local Wisdom in Bengkulu - Sinung Mufti Hangabei; Rangga Jayanuarto; Fahmi Arisandi (University Of Bengkulu Law Journal, 2025)
This research explores the integration of local wisdom in community-based disaster mitigation strategies in Bengkulu, an area prone to natural disasters such as earthquakes and tsunamis. Although local wisdom holds significant potential in reducing disaster risks, there are still gaps in its application within formal mitigation policies. A qualitative approach was used to explore local wisdom practices through ethnographic study, in-depth interviews, and policy document analysis. The findings indicate that while there have been some integration efforts, existing mitigation policies are primarily technical and do not fully account for the potential of local culture as a significant adaptive resource. The study also emphasizes the importance of community empowerment through culture-based education to enhance disaster preparedness and compliance with mitigation regulations. The integration of local wisdom with spiritual principles is expected to provide a strong legal foundation for involving communities in disaster mitigation efforts, creating a more holistic, effective, and sustainable approach